Mapeamento cartográfico do município de Paulo Jacinto-AL - Melo, Felippe Pessoa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The present study aims to confect the basemap of Paulo Jacinto county in the state of Alagoas. Technologies of Remote Sensing and Geographic Information System-GIS were used in the process, which enabled the manufacturing of a geographic database with matrix and vector information. This way, it is possible to perform the correlations between different data models in a single virtual environment, which maximizes the quality of the products originated in these interrelationships. Thematic maps were made regarding: hypsometry, drainage, vegetation, geology, soils, climate, isohyets, and isotherms. For possessing such material, the city of Paulo Jacinto-Al now has cartographic materials that facilitated decision making for implementation of public policies that are in line with sustainable development.